Preparation of RNAs with non-canonical 5′ ends using novel di- and trinucleotide reagents for co-transcriptional capping - Depaix, Anaïs; Grudzien-Nogalska, Ewa; Fedorczyk, Bartlomiej; Kiledjian, Megerditch; Jemielity, Jacek; Kowalska, Joanna (Frontiers in Molecular Biosciences, 2022)
Many eukaryotic and some bacterial RNAs are modified at the 5′ end by the addition of cap structures. In addition to the classic 7-methylguanosine 5′ cap in eukaryotic mRNA, several non-canonical caps have recently been identified, including NAD-linked, FAD-linked, and UDP-glucose-linked RNAs. However, studies of the biochemical properties of these caps are impaired by the limited access to in vitro transcribed RNA probes of high quality, as the typical capping efficiencies with NAD or FAD dinucleotides achieved in the presence of T7 polymerase rarely exceed 50%, and pyrimidine derivatives are not incorporated because of promoter sequence limitations. To address this issue, we developed a series of di- and trinucleotide capping reagents and in vitro transcription conditions to provide straightforward access to unconventionally capped RNAs with improved 5′-end homogeneity. We show that because of the transcription start site flexibility of T7 polymerase, R1ppApG-type structures (where R1 is either nicotinamide riboside or riboflavin) are efficiently incorporated into RNA during transcription from dsDNA templates containing both φ 6.5 and φ 2.5 promoters and enable high capping efficiencies (~90%). Moreover, uridine-initiated RNAs are accessible by transcription from templates containing the φ 6.5 promoter performed in the presence of R2ppUpG-type initiating nucleotides (where R2 is a sugar or phosphate moiety). We successfully employed this strategy to obtain several nucleotide-sugar-capped and uncapped RNAs. The capping reagents developed herein provide easy access to chemical probes to elucidate the biological roles of non-canonical RNA 5′ capping.